pH 조건에 따른 영지버섯(Ganoderma lucidum)의 물 및 에탄올 추출물의 β-Glucan 함량과 항산화능 - 김주영(Joo-Young Kim); 이상한(Sang-Han Lee); 정신교(Shin-Kyo Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Fruiting bodies of Ganoderma lucidum cultivated in Korea were reflux extracted at $90^{°}C$ using water and ethanol under different pH conditions. ${β}-Glucan$ contents, extraction yield, and antioxidant capacities of extracts were investigated. Antioxidant activities of water and ethanol extracts were measured by DPPH radical scavenging test and the FRAP method, along with their total phenolic contents and total flavonoid contents. Extraction time for the experiment was determined to be 6 h, and ${β}-glucan$ contents were the highest. Overall, ${β}-glucan$ contents of extracts increased with higher pH values, except those of 90% ethanol extracts (P<0.05). The yields and ${β}-glucan$ contents of ethanol extracts were lower than those of water extracts, and highest in water extract at pH 10 ($8.53{±}0.17%$, $6.20{±}0.12g/100g$, respectively). Ethanol extracts of fruiting bodies of G. lucidum showed stronger antioxidant capacities than water extracts (P<0.05). Especially, total phenolic contents of 30% ethanol extract at pH 10 was highest (35.06 GAE mg/g). Total phenolic contents of water and ethanol extracts showed good correlations with DPPH radical scavenging activities (r=0.969). 국내산 영지버섯으로부터 ${β}-glucan$ 소재 개발을 위하여 pH를 달리하여 물 및 에탄올로 $90^{°}C$에서 환류 추출하여, ${β}-glucan$ 함량과 항산화 활성 및 항산화 성분을 조사하였다. 물 추출물(pH 10)이 추출수율($8.53{±}0.17%$)과 ${β}-glucan$ 함량($6.20{±}0.12g/100g$)이 가장 높았다(P<0.05). 전반적으로 pH가 증가할수록 ${β}-glucan$ 함량이 증가하였으며 에탄올 추출물은 물 추출물보다 추출수율과 ${β}-glucan$ 함량이 낮았다. DPPH 라디칼 소거 활성과 FRAP 활성은 에탄올 추출물이 물 추출물보다 비교적 높았으며 pH 조건은 활성에 영향을 미치지 않았다(P<0.05). 총폴리페놀 화합물 및 총플라보노이드 화합물의 함량도 pH 조건에 상관없이 물 추출물보다 에탄올 추출물이 높았다. 물 추출물 및 에탄올 추출물들의 항산화 활성과 항산화 성분 값들은 비교적 높은 상관성을 보였으며, DPPH 라디칼 소거 활성과 총폴리페놀 화합물 함량 간의 상관성이 가장 높았다(r=0.969).